Design of Adaptive RFID RC522 on IoT Platform with Different Types Passive Tag Based on Self-Service Library Management System (SSLMS) - Ali K.; Rifai D.; Abdullah A.; Zain M.L.M.; Joraimee A.; Abdallah A.N.; Awang N.A.; Tan J.D.; Paw J.K.S.; Yaw C.T. (Penerbit Akademia Baru, 2024)
Radio Frequency Identification (RFID) refers to a wireless system comprising two components: tags and readers. The reader is a device with one or more antennas that emit radio waves and receive signals from the RFID tag. This system is available on most systems applications especially involving security systems, including house/office access systems, toll systems, and library systems. The accessing data is made stand-alone or data-based through the existing conventional RFID system on the market, especially in library systems. Also, the tag provided is only limited to the same type, either cards or stickers. From that, it will produce problems in monitoring the status of books, especially for loans or returns. At the same time, the difference in detection sensitivity will be the effect of the detection range for the types of tag used. Through this research, the development of adaptive RFID on IoT platforms with different types of passive tag library systems highly emphasized monitoring the status of books besides maximum range detection by using different types of passive tag and at the same time increasing the security by implementing the book status detection on the gate of the library. The tag sticker used can be read/written in the 13.56 MHz frequency with the High Frequency (HF) band due to its affordability and ease of implementation. RFID tags are embedded in all books and activated